Intrathecal pump refills at home or at the hospital: Protocol for a randomized controlled crossover trial—The IMPROVE study - Ulrike Van Hoey; Britt Winnepenninckx; Maarten Moens; Koen Putman; Lisa Goudman (PLoS ONE, 2026)
Background Intrathecal drug delivery (IDD) offers a therapeutic option for patients suffering from refractory pain or severe spasticity. By allowing targeted and continuous infusion directly into the intrathecal space, IDD bypasses the blood-brain barrier and enhances therapeutic effectiveness of the drug. Following the implantation of an IDD pump, the most commonly performed postoperative maintenance procedure is the pump refill (at regular intervals). This process can be burdensome for patients, affects their comfort, and carries significant risks. The current aim of this study is to evaluate whether intrathecal pump refills performed at home provide a difference in patient comfort compared to refills conducted in the hospital. Methods The IMPROVE study is a monocentric, randomized controlled crossover trial, including 82 patients. For this study, each patient will undergo four intrathecal pump refill procedures (two at home and two in the outpatient clinic) allocated in a randomized order. The primary objective of this study is to determine whether at-home refills provide a difference in patient comfort compared to hospital-based refills. Secondary objectives include assessing differences in quality of life, pain, stress, anxiety, self-efficacy, caregiver burden, patient preferences, safety, and overall cost-effectiveness between the two settings. Patients will be followed over the course of four intrathecal pump refills, which is estimated to span approximately one year. Discussion Within the IMPROVE project, pump refills will be performed through hospital at home. If at-home intrathecal pump refills prove more comfortable for patients and cost-effective for society, this would strengthen the patient-centred care model and support adopting this approach as the new standard treatment for IDD patients. A graphical abstract is provided in the supplementary materials (S1 Fig). Trial registration Details on the study site can be found at ISRCTN with identifier: ISRCTN18031921; [href: https://doi.org/10.1186/ISRCTN18031921 ] https://doi.org/10.1186/ISRCTN18031921 . The trial was registered in the ISRCTN registry on 18 November 2025.